Maternity and paternity leave for surgeons in Uruguay - Cerchiari, Emilia; Wagner, Gabriela; Rodríguez, Gabriela; Machín, Mariella (Cirugía del Uruguay, 2025)
Introduction: the increase of women in general surgery residency brings to discussion the subjects of pregnancy, maternity leave and child care. Maternity leave is associated with beneficial effects on the physical and mental health of mothers and children including decrease in infant mortality. It promotes initiation, maintenance and duration of breastfeeding. UNICEF recommends at least 18 weeks of paid maternity leave. In Uruguay public employees have 13 weeks of maternity leave. There are no publications about this subject in a national capacity. The aim of this article is to quantify the use of maternity and paternity leave primarily, and the use of part time for child care secondarily. Materials and methods: observational, descriptive, retrospective study. An anonymous survey with multiple choice questions was distributed to surgeons and surgical residents in Uruguay between August and October 2023. The results were processed in graphs and tables. Results: in the public sector. 35% of surveyed women took less than 3 months of maternity leave. This number is 39% in private institutions. Of all self-employed women, 65% took non-paid leave and 20% had no maternity leave. 39% of surveyed males did not take paternity leave; between those who did take it, 53% was for less than 10 days. Discussion: paid maternity leave benefits in newborns and mothers’ health are well established. There seems to be an underuse of maternity and paternity leave in the population surveyed, mainly in independent workers where the professionals lose this benefit. Conclusions: discussing maternity leave and its implications gives us an overview of the state of affairs that allows surgeons to work in favor of these rights.